ANALISIS PROPERTI PSIKOMETRI INTERNALIZED STIGMA OF EPILEPSY VERSI INDONESIA - Nova Dian Lestari,* Endang Mutiawati,* Etti Rahmawati,** Fitri Octaviana,*** Adang Bachtiar,**** Sya (Neurona Majalah Kedokteran Neuro Sains, 2017)
INTRODUCTION EPILEPSY IS STILL STIGMATIZING MEDICAL CONDITION WORLDWIDE STIGMA AFFECTS THE OUTPUT DETERIORATION SUCH AS SOCIAL ISOLATION UNEMPLOYMENT LACK OF OPPORTUNITY TO MARRY AND BECOMES A BARRIER FOR SEEKINGTREATMENT THERE HAS NOT BEEN ANY SCIENTIFIC DATA ON THE PERCEIVED LEVEL OF INTERNAL STIGMA OF EPILEPSY PATIENTS IN INDONESIA AN ACCURATE AND SIMPLE INSTRUMENT IN INDONESIAN VERSION IS NECESSARY TO DETECT THE LEVEL OF PERCEPTION OF INTERNAL STIGMA IN EPILEPSY PATIENTS